IMPLEMENTASI KEGIATAN TILAWAH AL-QUR’AN MENGGUNAKAN IRAMA NAHAWAND DI SMP MUHAMMADIYAH PROGRAM KHUSUS SURAKARTA - Fitria, Fitria; Ali Mustofa, Triono (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2023)
The purpose of this study is to describe the Qur'an recitation activities using nahawand rhythm through teacher guidance at SMP Muhammadiyah PK Surakarta. This research is a field research with qualitative type using phenomenon approach. Data were collected through interviews, observations, and documentation. Data validity was tested by triangulating techniques and triangulating sources. Data analysis begins with the data reduction stage, data presentation, conclusion drawing. The results showed that (1) The implementation of Qur'an recitation activities using nahawand rhythm at SMP Muhammadiyah PK Surakarta is an application or implementation that is organized and carried out regularly every day, not just extracurricular activities (2) The purpose of using nahawand rhythm in Qur'an recitation at SMP Muhammadiyah PK Surakarta is so that the school has a characteristic as an Islamic school (3) There are several factors in the implementation of Qur'an recitation activities using nahawand rhythm at SMP Muhammadiyah PK Surakarta, both in the form of inhibiting factors and supporting factors.